2010
DOI: 10.1093/rheumatology/keq088
|View full text |Cite
|
Sign up to set email alerts
|

Distinct bacterial colonization patterns of Escherichia coli subtypes associate with rheumatoid factor status in early inflammatory arthritis

Abstract: These studies link the type of colonizing bacteria in the gut and urine with the immune response (anti-bacterial and RF) in early-onset inflammatory arthritis and provide evidence for a role of the host-pathogen response in the aetiology of RF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…There is ongoing debate on whether RA may be initiated by an infectious microorganism,98 104 and many bacteria have been proposed in this capacity, such as Mycoplasma fermentans, 105 Escherichia coli 106 and Proteus mirabilis 107 108. This idea of ‘molecular mimicry’ has existed for at least a century, but has never been definitively proven 104.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…There is ongoing debate on whether RA may be initiated by an infectious microorganism,98 104 and many bacteria have been proposed in this capacity, such as Mycoplasma fermentans, 105 Escherichia coli 106 and Proteus mirabilis 107 108. This idea of ‘molecular mimicry’ has existed for at least a century, but has never been definitively proven 104.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The presence of speciic Escherichia coli, Mycoplasma fermentans, and Klebsiella pneumonia in the gut has been associated with RF positivity and has been linked to inlammatory arthritis in many ethnic populations [16].…”
Section: The Oral Sepsis Hypothesismentioning
confidence: 99%
“…On the one hand, there is much evidence that supports the association between RA and the intestinal microbiota; bacteria such as Mycoplasma fermentans [12], Escherichia coli [13], and Proteus mirabilis [14] have been reported to initiate the disease. On the other hand, it has been demonstrated that gastrointestinal and urogenital infections are associated with a significantly lowered risk of RA [15] and that patients with RA exhibit decreased gut microbial diversity compared with controls [16].…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 99%